PEMAHAMAN SEKOLAH TERHADAP KEBIJAKAN TENTANG PENYELENGGARAAN KURIKULUM SETARA JENDER - Ibrahim, Abdul Syukur (Universitas Muhammadiyah Surakarta, 2016)
The forming and development of educational curriculum must be fittedÂ with the reality and requirements of the stakeholders and the students by keepÂ referring to the national education standard and other national policies. ThisÂ research aims to describe objectively about the schoolâs understanding towardsÂ regulations number 20 year 2003 about references in national education curriculumÂ development and international ratifications made by Indonesian government.This research employs survey research plan with multistage area clusterÂ to 20 elementary school students as samples. In this research, the researcherplayed as the key instrument by referring to prepared questions and interviewÂ guidance. The result showed that the teachers and the principal have not gotsome proper understanding about the baseline of gender-equal curriculum policyÂ in Indonesian language subject. The schools need information about ways indeveloping the Indonesian language subject, wether as a tool for the applicationÂ of gender-equal curriculum and ways in developing gender-equal based IndonesianÂ language study program as a media to form a positive character and waysÂ in putting gender-equal values in Indonesian language subject.